KARAKTERISASI SUHU PEMANASAN SERBUK ZEOLIT UNTUK MENGIMOBILISASI UNSUR PB DALAM LARUTAN DENGAN ANALISIS MENGGUNAKAN LASER INDUCED BREAKDOWN SPECTROSCOPY (LIBS) - Utomo, Aji Priyo; Suyanto, Hery; Suharta, Wayan Gede (BULETIN FISIKA, 2016)
A research on the characterization of the heating temperature of the zeolite powder to immobilize Pb element in the solution by using LIBS analysis. This research aims to determine the optimum condition to heated zeolite powder in tho KBr substrate. Zeolite powder have to be to activated with the NaOH 1 M. After been the activation, that powder has been solited in tho Pb solution 1000 ppm and heating until the solution was used up  so left the zeolite powder with the Pb element. Then, the powder patched on the KBr and pressed in the pressure 400 kPa so became the pellet. The pellet heated in tho temperature 25 o C, 40 o C, 60 o C and 80 o C. After analyzed using LIBS, obtained the optimum temperature to heating the sampel is 60 o C.